2015
DOI: 10.1111/bjc.12077
|View full text |Cite
|
Sign up to set email alerts
|

Negative evaluations of self and others, and peer victimization as mediators of the relationship between childhood adversity and psychotic experiences in adolescence: The moderating role of loneliness

Abstract: Moderated mediation analyses poses an alternative framework to the understanding of trauma-psychosis associations Adolescent loneliness is a vulnerability factor within this association Data are based on a Northern Irish sample with relatively low levels of loneliness Cross-sectional data cannot explore the developmental course of these experiences in adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 79 publications
0
26
0
Order By: Relevance
“…Previous studies had already demonstrated repeatedly the role of traumatic childhood events in developing hallucinations (Longden et al ., ; Varese, Smeets, Drukker et al ., 2012) and also demonstrated the association of these traumas with hallucination proneness in healthy subjects (Perona‐Garcelán et al ., ). The findings of this study were similar to those of Murphy et al ., () who had already specifically related childhood memories of subtle experiences of threat and submissiveness to psychotic symptoms in adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies had already demonstrated repeatedly the role of traumatic childhood events in developing hallucinations (Longden et al ., ; Varese, Smeets, Drukker et al ., 2012) and also demonstrated the association of these traumas with hallucination proneness in healthy subjects (Perona‐Garcelán et al ., ). The findings of this study were similar to those of Murphy et al ., () who had already specifically related childhood memories of subtle experiences of threat and submissiveness to psychotic symptoms in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…These authors found similar processes associated with hallucinations and ideas of reference. In fact, in a review done by Read, van Os, Morrison and Ross (), traumatic experiences were found to be associated with several types of psychotic symptoms, and not just hallucinations, while Murphy, Murphy and Shevlin () found an association between childhood memories of threatening experiences and subordination and psychotic symptoms. They proposed a model in which victimization in adolescence and loneliness were mediating variables in that relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Most existing work has been in the general population, but one study suggests that loneliness mediates a relationship between internalised stigma and depression in people with psychosis, while another suggested that loneliness is a contextual moderator that may strengthen the trauma–psychosis relationship [91]. Other relevant psychological phenomena, such as motivation and level of perceived control/autonomy, were also highlighted as under-investigated.…”
Section: Other Research Prioritiesmentioning
confidence: 99%
“…Bullying victimization is a major global public health problem among adolescents that has been linked to a number of behavioral and emotional problems including anxiety (Cohen and Kendall, 2015), depression (Cole et al, 2014;Hamilton et al, 2016), loneliness (Campbell, 2013;Murphy et al, 2015;Storch and Masia-Warner, 2004), social withdrawal (Dill et al, 2004;Runions and Shaw, 2013), low self-esteem (Fredstrom et al, 2011;Jones et al, 2014;Tsaousis, 2016), as well as poor psychosocial adjustment (Nansel et al, 2001). Various meta-analytic studies have also found support for the link between bullying victimization and the onset of depressive symptoms and internalizing problems (Reijntjes et al, 2010;Ttofi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%